(untitled) (International Journal of Engineering and Computer Science, 2014)
Images are often corrupted by noises in the procedures of image acquisition and transmission. In this paper, an efficient denoising scheme and it’s VLSI architecture for the removal of noises is proposed. To achieve the goal of low complexity, a decision tree based impulse noise detector to detect the noisy pixels and an edge preserving filter to reconstruct the intensity values of noisy pixels is used. Furthermore histogram equalization is used to enhance the quality of images. The performance will be comparable to the higher complexity methods and the design requires only low computational complexity and suitable to be applied to many real time applications So final architecture consists of denoising and Image enhancement. Then this method is applied for different types of noises and compare results of image corrupted by impulses and equalized image using peak signal to noise ratio, mean square error, structural content.